(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The problem of liquefaction damages the structures which are constructed near the river. In order to minimize the damage caused to these structures in future this project is going to provide the necessary preliminary data that will help the civil engineers to incorporate such methods of construction which will minimize the effect of liquefaction of soils.